The U.S. Ecosystem‐Based Fisheries Management Policy and Road Map: Assessing Progress and Applying Lessons Learned - Chris J. Harvey; Yvonne L. deReynier; Wendy E. Morrison; Jennifer L. Cudney; Dorothy M. Dick; Travis Ford; Karla Gore; Jamison M. Gove; Elliott L. Hazen; Jerome M. Hermsen; Keith Kamikawa; Mandy Karnauskas; et al. (Fish and Fisheries, 2025)
The need for ecosystem‐based fisheries management (EBFM) is growing more urgent as environmental changes, species shifts, new ocean uses, and other factors force oceans toward novel states. In the United States, the National Oceanic and Atmospheric Administration's National Marine Fisheries Service (NOAA Fisheries) developed an EBFM Policy in 2016, accompanied by a Road Map of 49 action items, to support marine ecosystem‐based management and conservation of fisheries, habitats, and protected species under U.S. federal jurisdiction. In 2024, NOAA Fisheries updated its EBFM Policy and Road Map and formed a team of science and policy experts to review progress and derive lessons learned during the first Road Map iteration. Four key lessons emerged: (1) progress toward EBFM in the U.S. has been substantial; (2) greater coordination could further enhance progress; (3) more effort is required to link science to management activities; and (4) human dimensions need greater integration throughout EBFM implementation. Enabling factors for progress on the Road Map included: champions at both the leadership and staff levels; use of participatory processes; motivation driven by ecosystem shocks and threats; and leveraging existing processes and frameworks. The updated EBFM Road Map supports historic and ongoing efforts to implement U.S. laws through improved coordination, integration, and knowledge exchange and can help to address many urgent challenges facing U.S. marine fisheries, habitats, and protected resources.

Relating storm-snow avalanche instabilities to data collected from the Differential Emissivity Imaging Disdrometer (DEID) - Travis J. Morrison; Trent Meisenheimer; Timothy Garrett; Dhiraj Singh; Spencer Donovan; Eric Pardyjak (Cold Regions Science and Technology, 2023)

Boundary-Layer Processes Hindering Contemporary Numerical Weather Prediction Models - Marc Calaf; Nikki Vercauteren; Gabriel G. Katul; Marco G. Giometto; Travis J. Morrison; Fabien Margairaz; Vyacheslav Boyko; Eric R. Pardyjak (Boundary-Layer Meteorology, 2023)

The Heat-Flux Imbalance: The Role of Advection and Dispersive Fluxes on Heat Transport Over Thermally Heterogeneous Terrain - Travis Morrison; Eric R. Pardyjak; Matthias Mauder; Marc Calaf (Boundary-Layer Meteorology, 2022)

The Impact of Surface Temperature Heterogeneity on Near-Surface Heat Transport - Travis Morrison; Marc Calaf; Chad W. Higgins; Stephen A. Drake; Alexei Perelet; Eric Pardyjak (Boundary-Layer Meteorology, 2021)

Sub‐lethal temperature thresholds indicate acclimation and physiological limits in brook trout Salvelinus fontinalis - Scott M. Morrison; Theresa E. Mackey; Travis Durhack; Jennifer D. Jeffrey; Lilian M. Wiens; Neil J. Mochnacz; Caleb T. Hasler; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Journal of Fish Biology, 2020)
The upper thermal tolerance of brook trout Salvelinus fontinalis was estimated using critical thermal maxima (CT max ) experiments on fish acclimated to temperatures that span the species' thermal range (5–25°C). The CT max increased with acclimation temperature but plateaued in fish acclimated to 20, 23 and 25°C. Plasma lactate was highest, and the hepato‐somatic index ( I H ) was lowest at 23 and 25°C, which suggests additional metabolic costs at those acclimation temperatures. The results suggest that there is a sub‐lethal threshold between 20 and 23°C, beyond which the fish experience reduced physiological performance.